Relationship between reactive agility and change of direction speed in amateur soccer players - Matlák, J.; Tihanyi, J.; Rácz, L. (The Journal of Strength and Conditioning Research, 2016)
The aim of the study was to assess the relationship between reactive agility and change of direction speed (CODS) among amateur soccer players using running tests with four directional changes. Sixteen amateur soccer players (24.1 ± 3.3 years; 72.4 ± 7.3 kg; 178.7 ± 6 cm) completed CODS and reactive agility tests with four changes of direction using the SpeedCourt™ system (Globalspeed GmbH, Hemsbach, Germany). Countermovement jump (CMJ) height and maximal foot tapping count (completed in 3 seconds) were also measured with the same device. In the reactive agility test, participants had to react to a series of light stimuli projected onto a screen. Total time was shorter in the CODS test than in the reactive agility test (p < 0.001). Nonsignificant correlations were found among variables measured in the CODS, reactive agility, and CMJ tests. Low common variance (r2 = 0.03-0.18) was found between CODS and reactive agility test variables. The results of this study underscore the importance of cognitive factors in reactive agility performance and suggest that specific methods may be required for training and testing reactive agility and CODS.